PALEOMAGNETIC AND GEOCHRONOLOGICAL STUDY OF THE HALAQIAOLA BASALTS, SOUTHERN MARGIN OF THE ALTAI MOUNTAINS, NORTHERN XINJIANG: CONSTRAINTS ON NEOTECTONIC CONVERGENT PATTERNS NORTH OF TIBET - Huang B.; He H.; Zhang C.; Zhu R.; Piper J.D.A. (My University, 2006)
A combined geochronological and paleomagnetic study is reported from Miocene basalts from Halaqiaola and Paleocene to Eocene red beds from Fuyun at the southern Altai Mountains, northern Xinjiang. Three new 40Ar/39 Ar ages determined by fresh matrix from the Halaqiaola basalts collectively confirm the presence of Cenozoic magmatic activity in the northern Xinjiang. Alternating field and thermal demagnetization identify stable characteristic remanences with single reversed polarity in the basalts and red beds. Rock magnetic analysis identifies pseudosingle-domain titanomagnetites as carriers of remanence in the basalts. Paleomagnetic results from the Fuyun red beds indicate that inclination shallowing is present in this rock facies as also found in previous red bed studies from central Asia. In contrast, the time-averaged paleomagnetic direction from the basalts shows that no paleomagnetically discernible northward convergence has occurred north of Junggar since early Miocene times. Analysis of available Cretaceous and Cenozoic paleomagnetic data from volcanic rocks in central Asia shows that Neogene and Quaternary paleolatitudes are statistically concordant with predicted values from Eurasian references, suggesting that no significant northward convergence has occurred north of Tibet during the last 20 Myr. Cretaceous and Paleogene paleolatitudes lie ~5-6 ± 7° south of predicted values from the Eurasian path and suggest that neotectonic convergence of the order of several hundred kilometers has occurred north of the southwest Tian Shan. It is possible that neotectonic northward convergence north of Tibet will prove to be paleomagnetically undetectable, but more data are required to confirm this. Copyright 2006 by the American Geophysical Union.
Keywords: Quaternary; Cretaceous; Miocene; Eocene; Paleocene; Cenozoic::Quaternary; Кайнозой::Четвертичная; Mesozoic::Cretaceous; Мезозой::Меловая; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен